IMPLEMENTASI PENDEKATAN TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) BERBASIS 4C DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS XI SMAN 3 DENPASAR - Ida Ayu Agung Ekasiadi (Widyadari, 2026)
This study aims to describe the implementation of the 4Cs (critical thinking, creativity, collaboration, and communication)-based Technological Pedagogical and Content Knowledge (TPACK) approach in Indonesian language learning for eleventh-grade students at SMA Negeri 3 Denpasar. This study used a mixed methods approach with a sequential explanatory design, combining qualitative and quantitative data. Qualitative data were obtained through observation, interviews, and documentation studies, while quantitative data were collected through questionnaires. Data analysis was conducted using qualitative descriptive methods and descriptive statistics. The results indicate that the implementation of the 4Cs-based TPACK has been quite successful in the planning, implementation, and evaluation stages of learning. Pedagogical and content aspects have been effectively integrated, particularly in developing students' critical thinking and communication skills. However, the use of technology still tends to be more of a tool and has not been fully integrated in an innovative way. Furthermore, creativity and collaboration skills have not been optimally developed, and learning evaluation still focuses on the final results. The conclusion of this study indicates that the 4Cs-based TPACK approach has the potential to improve the quality of Indonesian language learning, but requires strengthening technology integration and the development of authentic assessments.